Optimizing Ummah Endowment Funds as a Pillar of Sustainable Development Goals: Analysis from the Perspective of Sharia Enterprise Theory - M. Fahmi Ashari Fahmi; Syefira Ramadhani Wardhana (Program Studi Magister Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Sunan Kalijaga, 2025)
This study aims to analyze the optimization of the management of the community's Ummah Endowment Fund as a pillar of sustainable development from a sharia perspective. This study uses qualitative research with descriptive analysis and literature study methods. Data was obtained from financial reports and data from BPKH, as well as related journal articles. The analysis was conducted using the sharia enterprise theory framework, which emphasizes the principles of tauhid, justice, trust, social welfare, and maslahah. The results of this study indicate that Ummah Endowment Funds have strategic potential as sustainable Islamic economic instruments. Second, sharia enterprise theory provides a comprehensive theoretical basis for understanding the holistic management of Ummah Endowment Funds. This theory provides a strong ethical framework for ensuring that fund management is not only financially efficient, but also fair, sustainable, and oriented towards the welfare of the people. Third, the factors affecting the effective utilization of Ummah Endowment Funds are governance, accountability and transparency, and innovation in sharia investment instruments. Fourth, the integration of the utilization of community Ummah Endowment Funds with Sharia enterprise theory can become an Islamic economic model that supports the sustainable welfare of the community. The implication of this study is that the application of sharia enterprise theory in the management of community Ummah Endowment Funds can strengthen social, economic, and environmental sustainability. The novelty of this study lies in the integration of the concept of sustainable development with sharia enterprise theory as a theoretical model for developing a more ethical, equitable, and beneficial governance of community Ummah Endowment Funds.